Role of Zinc Alpha2-Glycoprotein and Retinol-Binding Protein-4 in Iraqi Women with Thyroid Dysfunctions - Abd, Kawther A.; AL-Qaisi, Alaa Hussein J.; Hussein, Shaimaa A. (Iraqi Journal of Science, 2024)
Thyroid dysfunction (TD) and diabetes mellitus (DM) are two of the most frequent chronic endocrine disorders. This study included 60 women with thyroid disorders: 30 with hypothyroidism and 30 with hyperthyroidism, aged between 20 and 40 years. This study used 30 healthy women aged 20-40 years as a control group. Anthropometric measurements of Body Mass Index (BMI), hematological analysis of glycated hemoglobin (HbA1c), biochemical parameters (Thyroid-stimulating hormone TSH, Free triiodothyronine FT3, Free thyroxine FT4, Fasting Blood Sugar FBS), and adipokine concentrations zinc-α2-glycoprotein (AZGP-1) and retinol-binding protein-4 (RBP-4) were performed for all participants. The results revealed that the serum levels of zinc-α2-glycoprotein and retinol-binding protein-4 are significantly higher in hyperthyroidism (P<0.0001) compared to both healthy and hypothyroid women. Besides that, zinc-α2-glycoprotein has a negative correlation with TSH in the hyperthyroidism group. In the hypothyroidism group, it correlates positively with retinol-binding protein-4. In addition to that, retinol-binding protein-4 is positively correlated with FT3 and FT4 and negatively correlated with BMI in the hyperthyroidism group. For this reason, we conclude that these adipokines can aid in the diagnosis and monitoring of thyroid disorders, thereby preventing the onset of disease complications associated with type 2 diabetes mellitus. It is important to highlight that women with hypothyroidism are more likely than those with hyperthyroidism to develop diabetes.